Pelatihan Penguatan Kompetensi Guru Sekolah Dasar dalam Melaksanakan Penelitian Tindakan Kelas di Kota Pekanbaru - Hendri Marhadi; Erlisnawati Erlisnawati; Devi Risma; Donal Donal; Sisk Mardes; Matsuinda Matsuinda; Raudha Nur Hidayah Al Jannah; Vista Cindy; Samsinar Samsinar; Elvina Syahfrika; Raissa Khumaira; Sastra Anjani; Islahul Adila Rahma (Unri Conference Series: Community Engagement, 2025)
This activity aims to improve the professional competence of elementary school teachers in implementing Classroom Action Research (CAR) as an effort to strengthen teachers' reflective and innovative capacity in the learning process. The training was conducted at SD Negeri 147 Pekanbaru, involving 60 teachers from various elementary schools in Pekanbaru City. The activity implementation method used a participatory approach through several stages, namely initial observation, focus group discussion (FGD), training, mentoring, and evaluation. The results of the activity showed that the CAR training had a significant impact on improving teachers' understanding, motivation, and skills in preparing proposals and implementing CAR. Teachers gained direct experience in designing, implementing, and reporting research results relevant to learning problems in the classroom. This activity also fostered a collaborative culture among teachers and strengthened reflective abilities in continuously improving learning practices. Thus, CAR training and mentoring activities have proven effective as a strategy for developing teacher professionalism in realizing quality learning in elementary schools.